Dysmaturation of Somatostatin Interneurons Following Umbilical Cord Occlusion in Preterm Fetal Sheep - Ardalan, Maryam; Svedin, Pernilla; Baburamani, Ana A.; Supramaniam, Veena G.; Ek, Joakim; Hagberg, Henrik; Mallard, Carina (Frontiers in Physiology, 2019)
Introduction: Cerebral white matter injury is the most common neuropathology observed in preterm infants. However, there is increasing evidence that gray matter development also contributes to neurodevelopmental abnormalities. Fetal cerebral ischemia can lead to both neuronal and non-neuronal structural–functional abnormalities, but less is known about the specific effects on interneurons. Objective: In this study we used a well-established animal model of fetal asphyxia in preterm fetal sheep to study neuropathological outcome. We used comprehensive stereological methods to investigate the total number of oligodendrocytes, neurons and somatostatin (STT) positive interneurons as well as 3D morphological analysis of STT cells 14 days following umbilical cord occlusion in fetal sheep. Materials and Methods: Induction of asphyxia was performed by 25 min of complete umbilical cord occlusion (UCO) in 5 preterm fetal sheep (98-100 days gestational age). Seven, non-occluded twins served as controls. Quantification of the number of neurons (NeuN), STT interneurons and oligodendrocytes (Olig2, CNPase) was performed on fetal brain regions by applying optical fractionator method. A 3D morphological analysis of STT interneurons was performed using IMARIS software. Results: The number of Olig2, NeuN, and STT positive cells were reduced in IGWM, caudate and putamen in UCO animals compared to controls. There were also fewer STT interneurons in the ventral part of the hippocampus, the subiculum and the entorhinal cortex in UCO group, while other parts of cortex were virtually unaffected (p>0.05). Morphologically, STT positive interneurons showed a markedly immature structure, with shorter dendritic length and fewer dendritic branches in cortex, caudate, putamen and subiculum in the UCO group compared with control group (p<0.05). Conclusion: The significant reduction in the total number of neurons and oligodendrocytes in several brain regions confirm previous studies showing susceptibility of both neuronal and non-neuronal cells following fetal asphyxia. However, in the cerebral cortex significant dysmaturation of STT positive neurons occurred in the absence of cell loss. This suggest an abnormal maturation pattern of GABAergic interneurons in cerebral cortex might contribute to neurodevelopmental impairment in preterm infants and could implicate a novel target for neuroprotective therapies.